Community Empowerment Based on Branding Strengthening to Improve Rojolele’s Competitiveness Towards International Market - Rysca Indreswari; Dyah Ayu Suryaningrum; When -Chi Huang; Herlina Mega Herlina Puspitasari; Dian Rachmawanti Affandi; Dyah Yuni Kurniawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Klaten Regency is dominated by the agricultural sector, with paddy as its top commodity as much as 51,4% of the total area of 65,556 ha. Delanggu rice, namely Rojolele, has become the identity of Klaten as a local pride commodity from Klaten, Indonesia. Rojolele has special characteristics such as sticky, savory, and distinctive scent (aromatic). In addition, Rojolele has a unique value as part of national identity, culture, and local wisdom which has a huge opportunity to go global in the international market. Although it has been widely known worldwide, there are some challenges in its marketing development, especially in branding awareness. Many Rojolele riced produced by local SMEs in Klaten do not have business licenses yet, thus it hampers the marketing to the wider range area. The aim of the program is to strengthen the branding strategy to improve its competitiveness in the international market. The program will engage Sanggar Rojolele, a farming community in Delanggu Village that has replanted Rojolele Srinuk since 2016 as well as initiated many cultural events based on agriculture as one of local wisdom preservation in Klaten. Universitas Sebelas Maret engaged a close collaboration with the National Pingtung University of Science and Technology (NPUST) Taiwan trhough International Community Partnership (PKMI-UNS) to implement the community partnership program using the Participatory Rural Appraisal (PRA) method. The activity is divided into 5 steps, namely: 1) training of the business licenses and the importance of product diversification, which will be conducted using instructional and dialog methods; 2) a seminar of strategy to develop Rojolele towards the international market; 3) registration of business licenses of Rojolele and its derivative product; 4) developing an online market strategy of Rojolele; 5) monitoring, evaluation and program output dissemination. The program is expected to increase Rojolele’s market share globally as well as to improve Rojolele Srinuk brand awareness, thus raising its competitiveness in the global market.